Sunitinib induces early histomolecular changes in a subset of renal cancer cells that contribute to resistance. Issue 1 (27th August 2018) - Lichner, Zsuzsanna; Saleeb, Rola; Butz, Henriett; Ding, Qiang; Nofech-Mozes, Roy; Riad, Sara; Farag, Mina; Varkouhi, Amir K.; dos Santos, Claudia C.; Kapus, András; Yousef, George M.
ABSTRACT: Sunitinib is the standard‐of‐care, first‐line treatment for advanced renal cell carcinoma (RCC). Characteristics of treatment‐resistant RCC have been described; however, complex tumor adaptation mechanisms obstruct the identification of significant operators in resistance. We hypothesized that resistance is a late manifestation of early, treatment‐induced histomolecular alterations; therefore, studying early drug response may identify drivers of resistance. We describe an epithelioid RCC growth pattern in RCC xenografts, which emerges in sunitinib‐sensitive tumors and is augmented during resistance. This growth modality is molecularly and morphologically related to the RCC spheroids that advance during in vitro treatment. Based on time‐lapse microscopy, mRNA and microRNA screening, and tumor behavior‐related characteristics, we propose that the spheroid and adherent RCC growth patterns differentially respond to sunitinib. Gene expression analysis indicated that sunitinib promoted spheroid formation, which provided a selective survival advantage under treatment. Functional studies confirm that E‐cadherin is a key contributor to the survival of RCC cells under sunitinib treatment. In summary, we suggest that sunitinib‐resistant RCC cells exist in treatment‐sensitive tumors and are histologically identifiable.—Lichner, Z., Saleeb, R., Butz, H., Ding, Q., Nofech‐Mozes, R., Riad, S., Farag, M., Varkouhi, A. K., dosSantos, C. C., Kapus, A., Yousef, G. M. Sunitinib induces early histomolecular changes in a subset of renal cancer cells that contribute to resistance. FASEB J. 33, 1347–1359 (2019). www.fasebj.org